Faculty Perceptions of Persons with Disabilities and Students with Special Needs in the New Normal: Basis for Drafting Advocacy Program in Philippine State Universities and Colleges - Zuniga-Tonio, Jimmylen (International Journal of Social and Administrative Sciences, 2022)
As the world’s largest minority, people with disabilities (PWD) students and students with special needs face additional challenges to become successful in higher education during the COVID-19 pandemic. This study investigated faculty attitudes toward these students in the new normal. Specifically, the study looked at how faculty perceived PWDs and their knowledge, experiences, and opinions about them, as well as their willingness to make significant accommodations. Ninety faculty members from a state university were surveyed and the results revealed that faculty members generally perceive that they are considerate of the requests of students who have disabilities and special needs. Likewise, findings showed that faculty members are willing to: (1) set up extended time exams; (2) give these students extra time to complete assignments; (3) alter the way exams are answered; (4) permit these students to tape record lectures; and (5) spend additional time with these students to clarify course-related material.